2014
DOI: 10.1073/pnas.1420103111
|View full text |Cite
|
Sign up to set email alerts
|

Potential function for the Huntingtin protein as a scaffold for selective autophagy

Abstract: Although dominant gain-of-function triplet repeat expansions in the Huntingtin (HTT) gene are the underlying cause of Huntington disease (HD), understanding the normal functions of nonmutant HTT protein has remained a challenge. We report here findings that suggest that HTT plays a significant role in selective autophagy. Loss of HTT function in Drosophila disrupts starvationinduced autophagy in larvae and conditional knockout of HTT in the mouse CNS causes characteristic cellular hallmarks of disrupted autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
228
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(256 citation statements)
references
References 66 publications
15
228
0
4
Order By: Relevance
“…1,3,8 Important recent findings also describe a potential function as a scaffold for multiple autophagyassociated proteins in selective autophagy. 11 Consistent with these putative functions, HTT contains multiple leucinerich HEAT repeats that are involved in protein-protein interactions. 12,13 The exact nature of the polyQ-HTT toxic gain of function remains elusive, but several possibilities have been identified.…”
Section: Open Questionsmentioning
confidence: 96%
“…1,3,8 Important recent findings also describe a potential function as a scaffold for multiple autophagyassociated proteins in selective autophagy. 11 Consistent with these putative functions, HTT contains multiple leucinerich HEAT repeats that are involved in protein-protein interactions. 12,13 The exact nature of the polyQ-HTT toxic gain of function remains elusive, but several possibilities have been identified.…”
Section: Open Questionsmentioning
confidence: 96%
“…Similar to Atg11, ALFY (autophagy-linked FYVE protein) is a scaffolding protein implicated in aggrephagy that links cargo to the autophagic machinery (Isakson et al, 2013). Moreover, Huntingtin (HTT) has been proposed to serve as adaptor for any type of selective autophagy, because the domain of HTT shares structure similarities and binding activity with the yeast Atg11 protein and interacts with autophagic effector proteins (Ochaba et al, 2014). It is tempting to speculate that ALFY or HTT are part of the RPC mediating HIF-2α-induced pexophagy and thus, functioning as scaffold protein(s).…”
Section: Models How Hif-2α Might Trigger Pexophagymentioning
confidence: 99%
“…Recent studies have demonstrated an intrinsic connection between selective autophagy impairment and neurodegenerative diseases, including Alzheimer's disease (AD) [4][5][6][7] , Parkinson's disease (PD) [8][9][10] , Huntington's disease (HD) [11][12][13][14] , amyotrophic lateral sclerosis (ALS) [15][16][17] , and multiple sclerosis (MS) [1,[18][19][20][21][22][23] .…”
mentioning
confidence: 99%
“…HD is caused by expansion of a CAG trinucleotide repeat in the first exon of the huntingtin gene that encodes the mutant huntingtin: this protein is highly expressed in neurons and participates in many cellular functions, including vesicle and organelle transport and autophagy [13,27] . Mutant huntingtin interferes with the correct autophagic function; therapeutic strategies that improve the clearance of this mutant protein by autophagy reduce neuronal toxicity [14] .…”
mentioning
confidence: 99%